PEMBELAJARAN MODEL MIND MAP UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KOMPETENSI SISTEM KELISTRIKAN DAN INSTRUMEN SISWA KELAS XI TEKNIK SEPEDA MOTOR SMK DIPONEGORO DEPOK SLEMAN - Iswanto Iswanto; Pairun Roniwijaya (Jurnal Taman Vokasi, 2017)
The aims of this research are to increase: (1) the activity of students of class XI Motorcycle Engineering Program In SMK Diponegoro Depok Sleman on the electrical system and instrumen lesson through mind map learning model; and (2) the learning outcomes of students of class XI Motorcycle Engineering Program In SMK Diponegoro Depok Sleman on the electricalsystem and instrumen lesson through mind map learning model. This research was conducted atSMK Diponegoro Depok Sleman. The subject ofthis research are students offOdd Semester class XI TSM 2014/2015 academic year. Object ofthis study is Mind Map model to improved learning activities and learning outcomes. The type of this research is the Classroom Action Research (CAR) conducted in three cycles, each cycle consists of planning, execution (interview,observation, documentation and testing), observation and reflection. Data collection techniques used observation sheet and achievement test. The data were analyzed using quantitative analysis.The results of this study concluded that: (1) application of the mind map learning model canenhance the activity of learning, this is evidenced by the average student activity presentations onfirst cycle is 28,4%, on second cycle 60,2% and the third cycle is 86,4%; and (2) application ofthe mind map learning model can improve the learning outcomes of competences electricalsystems and instrument, this is evidenced by the average value of learning outcomes preaction is62.65, the average value of learning outcomes of the first cycle is 71.87, the average value oflearning outcomes of the second cycle 81.09, and the average value of learning outcomes of the third cycle 88.1